Oriented Neural Spheroid Formation and Differentiation of Neural Stem Cells Guided by Anisotropic Inverse Opals - Xia, Lin (Front Bioeng Biotechnol, 2020)
Isotropic inverse opal structures have been extensively studied for the ability to manipulate cell behaviors such as attachment, migration, and spheroid formation. However, their use in regulate the behaviors of neural stem cells has not been fully explored, besides, the isotropic inverse opal structures usually lack the ability to induce the oriented cell growth which is fundamental in neural regeneration based on neural stem cell therapy. In this paper, the anisotropic inverse opal substrates were obtained by mechanically stretching the poly (vinylidene fluoride) (PVDF) inverse opal films. The anisotropic inverse opal substrates possessed good biocompatibility, optical properties and anisotropy, provided well guidance for the formation of neural spheroids, the alignment of neural stem cells, the differentiation of neural stem cells, the oriented growth of derived neurons and the dendritic complexity of the newborn neurons. Thus, we conclude that the anisotropic inverse opal substrates possess great potential in neural regeneration applications.